Ecosystem metabolism and nutrient dynamics in the main channel and backwaters of the Upper Mississippi River. (9th June 2015) - Houser, Jeffrey N.; Bartsch, Lynn A.; Richardson, William B.; Rogala, James T.; Sullivan, John F.
Summary Photosynthesis and respiration are primary drivers of dissolved oxygen dynamics in rivers. We measured dissolved oxygen dynamics, aquatic ecosystem metabolism, algal abundance and nutrient concentrations at main channel and backwater sites on a reach of the Upper Mississippi River that borders the states of Wisconsin and Minnesota (U.S.A.). We asked (i) how ecosystem metabolism rates, dissolved oxygen dynamics and nutrient concentrations differed in the main channel and in backwaters, (ii) whether ecosystem metabolism relates to solar irradiance, nutrient concentration, algal abundance, temperature and river discharge and (iii) whether the relationships between ecosystem metabolism and these environmental factors differs between the main channel and backwaters. The rates of aquatic ecosystem metabolism in the main channel were among the highest reported for large rivers. Mean daily gross primary production (GPP), ecosystem respiration (R) and net ecosystem production (NEP) in the main channel in the 2006 growing season were 10, 6 and 4 g O2 m2 d−1, respectively. Solar irradiance, discharge and temperature, rather than nutrients, accounted for most temporal variability in gross primary production (GPP). Discharge was negatively associated with GPP in the main channel and temperature positively associated with GPP in backwaters. Primary production consistently exceeded respiration in the main channel in summer, resulting in persistent oxygen supersaturation from late June to early August. Maximum chlorophyll concentrations (˜140 μg L−1) were observed in the main channel, rather than the backwaters. Nitrogen and phosphorus exhibited contrasting temporal patterns in backwaters probably reflecting differences in their sources and sinks; N declined during the growing season while P increased.